The Contemporary Foster Care Legislative Framework in Greece: A Review of its Assets and Weaknesses - Farmakopoulou, Ignatia; Baltsioti, Vasiliki (Technium Social Sciences Journal, 2024)
This review comprehensively analyzes the contemporary Greek legislative foster care system according to N4538/2018, exploring all the relevant international agreements such as the United Nations Convention on the Rights of the Child and the European Union’s Charter of Fundamental Rights, that influenced its enactment. It highlights the rights and protection afforded to children in foster care, detailing provisions from the Hague Convention on the Rights of the Child and European legislation. It explores thoroughly the recent legislative reforms in Greece, including the establishment of the National Council for Foster Care and Adoption. It emphasizes the development and adherence to National and Special Registers for minors in the modern Child Protection System, as well as the implementation of Individual Family Rehabilitation Plans. It reveals that the recent legislation framework has many advantages but also a few weaknesses that could be amended. The legal procedures and criteria for placing minors in fostering in Greece, and the required criteria to ensure that foster parents meet the necessary guidelines to protect the best interests of children are discussed. This paper also examines the legal and procedural steps required to link children to foster families, the arrangements for supervision of foster parents and the consequences of fostering in cases of non-compliance. It is also proven that social workers play a key role in all stages and procedures of the application of the institution of foster care since they have taken up the main responsibilities for its implementation, prior, during and after the children are placed in foster parents. The article concludes that there is an imperative need for informed policies and practices that will ensure the adequate care and protection of minors in the foster system, recommending a synergy of legal, institutional, and educational strategies to optimize the welfare of foster children and support foster parents.